2022
DOI: 10.2459/jcm.0000000000001345
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of ticagrelor compared to clopidogrel in improving endothelial function in patients with coronary artery disease: a systematic review

Abstract: BackgroundTicagrelor and clopidogrel are antiplatelet drugs that act by binding to the adenosine diphosphate P2Y12 receptor. Previous studies have compared between them regarding the endothelial function effect.ObjectivesThis systematic review aims to summarize the evidence comparing the efficacy of ticagrelor vs. clopidogrel in improving endothelial function in patients with coronary artery disease (CAD).MethodsIn August 2021, the Scopus, PubMed, Web of Science, and Cochrane library were searched systematical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, the findings of ticagrelor on FMD are not consistent. Ticagrelor was shown to improve FMD compared with clopidogrel after just 1-month treatment in the article by Ariotti et al 8 On the contrary, no significant effect was found in the article by Schnorbus et al 9 Anyway, as shown by Albadrani et al , 6 the large majority of biomarkers support the effect of ticagrelor on endothelial function, and we may assume the existence of a positive modulation with potential clinical benefit.…”
mentioning
confidence: 91%
See 4 more Smart Citations
“…However, the findings of ticagrelor on FMD are not consistent. Ticagrelor was shown to improve FMD compared with clopidogrel after just 1-month treatment in the article by Ariotti et al 8 On the contrary, no significant effect was found in the article by Schnorbus et al 9 Anyway, as shown by Albadrani et al , 6 the large majority of biomarkers support the effect of ticagrelor on endothelial function, and we may assume the existence of a positive modulation with potential clinical benefit.…”
mentioning
confidence: 91%
“…6,7 On the other hand, ticagrelor was not significantly related to significant changes in reactive hyperemia index (RHI) and some biomarkers including circulating endothelial cells (CEC), white blood cells/CEC (WBC/CEC), WBC/endothelial progenitor cell (WBC/EPC) levels, endothelin-1, and soluble CD40 ligand. 6 Finally, results for flow-mediated dilatation (FMD) and EPC levels were conflicting. 6,8 The results of this systematic review raise two important questions: What is the global effect of ticagrelor on endothelial function considering that we have discordant results between different tests?…”
mentioning
confidence: 98%
See 3 more Smart Citations